Участь бікарбонату в регуляції фотохімічних реакцій в хлоропластах шпинату - Подорванов, В.В.; Золотарьова, О.К.; Чорноштан, О.А. (Український фітоценологічний збірник, 2006)
Известно, что бикарбонат стимулирует фотохимические реакции в хлоропластах. В тилакоидах найдено по крайней мере два пула связанного бикарбоната: прочно связанный (1 НСО3 — на 400-600 молекул хлорофилла) контролирующий фотохимическую активность ФС2 и слабо связанный (1 НСО3 — на 1 молекулу хлорофилла), который может быть удален без существенного влияния на фотохимическую активность ФС2. Функциональная роль слабо связанного бикарбоната неизвестна. Целью настоящей работы было исследование взаимосвязи между количеством мембраносвязанных HCO3 — ионов и светоиндуцированного протонного поглощения (ΔH+) в суспензии изолированных хлоропластах шпината. Ингибиторы КА гидрофильный ацетозоламид и липофильный этоксизоламид снижали количество связанного бикарбоната и подавляли величину ΔH+ в диапазоне pH 6,0-8,0. Сделан вывод, что пул слабосвязанного бикарбоната контролирует свето-зависимый протонный транспорт в хлоропластах. It is known that bicarbonate stimulates photochemical reactions in chloroplasts. There is at least two pools of bound bicarbonate with different affinity of its binding to thylakoids, and evidently only the high-affinity one (1 НСО3 — per 400—600 Chl molecules) controls photochemical reactions in PS2. Interpretations of the stimulating effect of bicarbonate on the activity of PS2 are contradictory, and the functional role the lower-affinity pool (close to Chl concentration) which can be removed without essential effect for PS2, remains unknown. The aim of the present work was investigation of relationship between the amount of the membrane-bound HCO3 — ions and light-induced proton uptake (ΔH+) by suspension of isolated spinach chloroplasts. The inhibitors of carboanhydrase hydrophyllic acetazolamide and lipophyllic ethoxyzolamide both reduced the amount of bound bicarbonate and suppressed ΔH+ in 6,0—8,0 pH range. It is concluded that lower-affinity pool of bound bicarbonate controls light-dependent proton transport in chloroplasts.